O conceito de estado e a fundamentação do estado de direito em Kant e Kelsen - Lima, Newton de Oliveira (2015)
The theory of Hans Kelsen's Law came from Kant who gave the law the power to coerce the freedom under the law in order to ensure the freedom of all. So Kelsen defined the law as State’s “pure” coercive order and defended the unity of Law and State. The purpose of the thesis is to rethink Kelsen’s legitimacy solution law and, by criticizing it, resume Kantian reflection aimed at protecting political freedom with a citizens' function: the response to the State by a 'critical freedom' able to take the proposition against standards by political individual to parliament. In defended proposal, the political freedom of the subject theory possesses sufficient powers to criticize the State within constitutional limits, but maintaining state sovereignty. In Kant liberal basis in policy implies the idea of political freedom as the founding of the state, this is the guardian of the law as a normative body. For Kant, the application of legal-rational principles within the legal procedures is of fundamental importance to ensure the republican function of the state, which is the fulfillment of the Constitution and the state unity by maintaining the original political contract. We understand that in Kant legitimizing the state is to support it in the innate freedom expressed in its legal and practical function as political freedom, being that effective form of protection involves interpreting the legal-rational principles by giving them a function "critical" in drafting a proposed citizenship contestation to the State. Thinking of political judgments delivered by the citizens as a directly normative possibility makes them keep the State in Law limits as an expression of political freedom.